State corporation income taxation: An economic perspective on Nexus - David E. Wildasin (Center for Economic Studies and ifo Institute (CESifo), 2010)
Acting in the interest of their residents, within limits imposed by Federal statute and by the Constitution, states have incentives to impose taxes on the profits of corporations owned by nonresidents. This paper presents a model within which a state, using an apportionment formula that includes a sales factor, would choose to tax the income of out-of-state corporations that derive revenues from the sale or licensing of intangible assets to in-state customers, provided that such corporations have sufficient nexus to be taxable. Although such policies enable states to capture rents from nonresidents, they also introduce tax distortions by imposing implicit tariffs on sales by out-of-state firms.
Keywords: H25; H71; K34; 330; Steuerpolitik; Unternehmensbesteuerung; Multinationales Unternehmen; Immaterialgüterrechte; Öffentliche Einnahmen; Theorie